Effectiveness of Soursop Leaf and Seed Extract (Annona muricata) and its Combination on Antifeeding Activity and Mortality of Spodoptera frugiperda Larvae - Ramadan, Almas Rusfi Sagita; Yuliani, Yuliani (LenteraBio : Berkala Ilmiah Biologi, 2025)
Spodoptera frugiperda is a new pest that is very influential in decreasing corn production. Bioinsecticide from soursop leaves and seeds is one alternative to control S. frugiperda because it contains acetogenin, alkaloids, tannins, flavonoids, and saponins. This study aimed to determine the effectiveness and interaction between soursop leaf and seed extracts and their combination against mortality and anti-feeding activity of Spodoptera frugiperda larvae. This study uses a 2-factor CRD, its extracts soursop leaf, soursop seeds, and their combinations; the concentration of the extract is 20%, 30%, and 40%. Negative control with aqua dest and positive control with chlorantraniliprole pesticide. The parameters of this study were larval anti-feeding activity and larval mortality. The mortality and anti-feeding activity percentage were transformed by arcsin, analyzed using 2-Way ANOVA, and further examined with the Duncan test on IBM SPSS 25. The results of this study revealed the influence and interaction between extract type and concentration on the mortality and anti-feeding activity of S. frugiperda larvae. The 40% concentration combination extract was the best because it produced 60.42% anti-feeding activity and 96.67% mortality. Therefore, soursop seed and leaf extracts can be recommended as bioinsecticides to replace chemical insecticides.